Stand alone power supply / Muhammad Ali Raydha Othman & Muhammad Aqmal Hakkim Ajman - Othman, Muhammad Ali Raydha; Ajman, Muhammad Aqmal Hakkim (2015)
The main objective of our project is to change the supply energy of any small voltage gadgets. to become a stand alone device for a very long lasting purpose. Therefore, we add an alternative supply input to the gadgets. From adding another non-renewable energy, we make an improvise by providing a renewable energy resources to the device like a phone charger. One of the renewable energy is solar energy that can be converted to electrical energy by using a solar panel. However, by using solar panel there is still some modification needed to be done. In some moment the solar panel cannot produce a productive energy for given output because of the movement of sun from east to the west. Therefore an upgrade is apply to the solar panel by adding a motor to the panel so that it can rotate according to the movement of the sun. By doing so, the solar panel can absorb full intensity of light. In conclusion, any device like phone charger is commonly use, therefore several improvement is needed to the device to make it more efficient and perform well in any type of condition.